Part 2: biocompatibility evaluation of hydroxyapatite-based clinoptilolite and Al2O3 composites - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (SPRINGER, 2017)
The biocompatibility of clinoptilolite/alumina/bovine hydroxyapatite (Cp - Al2O3 - BHA) composite, at different ratio obtained by powder pressing process, were investigated studying the behavior of osteosarcoma (SAOS-2) cells. The biocompatibility was examined by means of cytotoxicity and cytocompatibility tests. The structure and morphology of bioceramic composites were studied by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) technique. The results showed that these materials have no toxic effects. The natural composite that fabricated in this study may be a promising approach for bone engineering applications.
Keywords: Bovine hydroxyapatite; Clinoptilolite; Alumina; Biocomposites; Biocompatibility; MECHANICAL-PROPERTIES; NATURAL ZEOLITE; BEHAVIOR; SIO2